Exonuclease-assisted target recycling for ultrasensitive electrochemical detection of microRNA at vertically aligned carbon nanotubes. Issue 23 (4th June 2019) - Chen, Zhichao; Xie, Yiming; Huang, Wan; Qin, Chuanying; Yu, Aimin; Lai, Guosong
Abstract : The one-step biorecognition at a vertically aligned SWCNT-based biosensor and T7 exonuclease-assisted target recycling enable the ultrasensitive bioassay of microRNA-21. Abstract : As an important biomarker for early disease diagnosis, microRNA-21 (miRNA-21) has attracted considerable attention owing to its accurate detection. Herein we combine the one-step biorecognition reaction at a vertically aligned nanostructure-based biosensor with the T7 exonuclease (Exo)-assisted target recycling to develop a novel electrochemical bioassay method for miRNA-21 detection. The vertically aligned nanointerface is constructed through the covalent attachment of terminally carboxylated single-walled carbon nanotubes (SWCNTs) at an aryldiazonium salt-modified electrode, which enables the noncovalent adsorption of a ferrocene-labeled single-stranded signal DNA to obtain the biosensor. Upon its incubation with a target miRNA-21 solution, DNA/RNA hybridized duplexes will form and release from the electrode surface, leading to the corresponding electrochemical signal decrease of the biosensor. Moreover, this biorecognition reaction can also trigger the T7 Exo-assisted target recycling to achieve great signal amplification. Together with the highly efficient biorecognition and excellent electron transfer promotion at the vertically aligned SWCNTs, this biosensor exhibits a wide linear range varying from 0.01 to 100 pM and a low detection limit down to 3.5 fM. Considering its obvious performance superiority and convenient manipulations, this vertically aligned SWCNT-based electrochemical biosensing method has extensive potential for practical applications.